2015
DOI: 10.5858/arpa.2014-0262-oa
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Angiogenic Factors in Invasive Retinoblastoma Tumors Is Associated With Increase in Tumor Cells Expressing Stem Cell Marker Sox2

Abstract: Context Progression of retinoblastoma is associated with increased tumor angiogenesis. However, a clear relationship between the expression of angiogenic markers in specific regions of the tumor and tumor progression has not been established. This study investigates the association between angiogenic factors in retinoblastomas with choroidal and/or optic nerve invasion (high-risk/invasive retinoblastoma) and expression of Sox2, a stem cell marker. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…*P < 0.05, **P < 0.01. transcription factor KLF4 not only promotes cancer stem cell-like characteristics in osteosarcoma 30 but also mediated sprouting angiogenesis via Notch 20 . In retinoblastoma tumor, stemness-related SOX2 was associated with eyes with higher VEGF-A expression and tumor invasiveness 31 . Whether SOX2 is capable of modulating angiogenesis and VM in CRC needs to be explored further.…”
Section: Discussionmentioning
confidence: 93%
“…*P < 0.05, **P < 0.01. transcription factor KLF4 not only promotes cancer stem cell-like characteristics in osteosarcoma 30 but also mediated sprouting angiogenesis via Notch 20 . In retinoblastoma tumor, stemness-related SOX2 was associated with eyes with higher VEGF-A expression and tumor invasiveness 31 . Whether SOX2 is capable of modulating angiogenesis and VM in CRC needs to be explored further.…”
Section: Discussionmentioning
confidence: 93%
“…Histopathologically, retinoblastoma tumor shows perivascular sleeves consisting of neoplastic cells, demonstrating a close association of tumor cells with blood vessels 24 . High vascularization in retinoblastoma has been shown to be linked with chemoresistance, dissemination and poor prognosis 16 , 25 . In contrast, angiogenesis inhibition alone by bevacizumab or pigment epithelium-derived factor suppresses retinoblastoma growth without producing significant systemic toxicity 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%
“…11 VEGF-A expression in the present study did not show a statistically significant correlation with HRF (P ¼ 0.06). However, Garcia et al 19 demonstrated that HRF retinoblastoma tumors elicited more angiogenesis than non-HRF tumors as they expressed more VEGF, especially in the tumor and iris. Similarly, Areán et al 10 reported on a positive correlation between VEGF staining intensity and time of progression and mitotic and apoptotic indexes.…”
Section: Discussionmentioning
confidence: 99%
“…LRG-1 binds directly to the TGF-b accessory receptor endoglin (CD105), which in the presence of TGF-b1 results in promotion of the proangiogenic Smad1/5/8 signaling pathway. 11 Endoglin expression in retinoblastoma was studied by Garcia et al 19 It was found to be expressed in low levels in the HRF and non-HRF tumors and in the nonneoplastic retina. Its significant expression, however, was observed in the iris neovascular membranes of HRF retinoblastomas.…”
Section: Discussionmentioning
confidence: 99%